Gendered perspectives of restorative justice, violence and resilience : an international framework - Orton, Bev (Diverse perspectives on creating a fairer society, 2023)
Research on Restorative Justice to date tends to be gender blind. Gendered Perspectives of Restorative Justice, Violence and Resilience: An International Framework addresses this lack of gender awareness by sharing the personal journeys and experiences of women from across the Global South. Combining narratives of gendered Restorative Justice, gender-based violence, women's resilience, activism and healing along with empirical and theoretical analyses, contributors raise awareness and educate readers about the benefits of framing Restorative Justice as an intervention for understanding the resilience of women facing violence, political challenges and sexual assault. Within a truly international framework, chapters highlight significant scholarship from researchers with diverse backgrounds, opening a sociological dialogue onto this critical issue. From discussion of criminal cases of sexual violence in India, to victims of Intimate Partner Violence in Singapore, to the experiences of sex workers in South Africa, Gendered Perspectives of Restorative Justice, Violence and Resilience: An International Framework shines crucial visibility on a diverse, gendered lens of intervention, empowerment and understanding of violence and resilience. Providing an in-depth, international perspective of women's resilience, and focusing on women as active participants in the process of Restorative Justice, Gendered Perspectives of Restorative Justice, Violence and Resilience: An International Framework is must-have reading for academics, practitioners and policymakers, as well as anyone seeking to augment their allyship.